Probucol mitigates high-fat diet-induced cognitive and social impairments by regulating brain redox and insulin resistance - Wu, Han-Ming; Yang, Yang Vivian; Huang, Na-Jun; Fan, Li-Ping; Dai, Ying-Ying; Hu, Ke-Ting; Tang, Tian-Yu; Liu, Lin; Xu, Yue; Liu, Dong-Tai; Cai, Ze-Xin; Niu, Xiao-Yu; et al. (Frontiers in Neuroscience, 2024)
Probucol has been utilized as a cholesterol lowering drug with antioxidative properties. However, the impact and fundamental mechanisms of probucol in obesity-related cognitive decline is unclear.Here, we show that probucol treatment effectively alleviates cognitive and social impairments induced by a high-fat diet (HFD) in mice, while exhibiting no discernible influence on mood-related behaviors. Notably, the beneficial effects of probucol arise independent of rectifying obesity or restoring systemic glucose and lipid homeostasis, as evidenced by the lack of changes in body weight, serum cholesterol levels, blood glucose, hyperinsulinemia, systemic insulin resistance, and oxidative stress. Instead, probucol could regulate the levels of nitric oxide and superoxide-generating proteins, and it could specifically alleviate HFD-induced hippocampal insulin resistance. These findings shed light on the potential role of probucol in modulating obesity-related cognitive decline, and urge reevaluation of the underlying mechanisms by which probucol exerts its beneficial effects.